Can internet usage ease the process of learning engineering subjects?: A study on students of diploma in mechanical engineering / Dzullijah Ibrahim and Peridah Bahari - Ibrahim, Dzullijah; Bahari, Peridah (2004)
Engineering subjects are often being labelled as ‘difficult’ subjects. Many references either in hardcopy of softcopy form confused the diploma level students further as it might be written for higher levels. New educational possibilities provided by the Internet can transform the process of learning and teaching engineering subjects. A study on students of Diploma in Mechanical Engineering for Automation and Mathematical Engineering subjects reveals that they can use the Internet to enhance their educational experience in variety of ways. This paper at the same time sought to identify the limitations and related issues of using Internet for education. Recommendations are made about informing and training students on IT as the first step in promoting the Internet usage at the early stage of learning Engineering subjects.